Evaluation of Features for Ground Glass Opacities in Lung Cancer Patients Positive with Covid-19 (Medical Forum Monthly, 2022)
Objective: To evaluate radiological features of Covid-19 and early lung cancer through High-resolution computed tomography (HRCT) and demonstrate the disparity between them.Study Design: A retrospective studyPlace and Duration of Study: This study was conducted at the Covid-19 ward, Oncology, Radiology Ward of Nishtar Medical University & Hospital Multan from 12th Nov 2019 to 12th Nov 2020.Materials and Methods: A total of 100 Covid-19 patients and 300 patients with pulmonary ground-glass opacities undergoing lung surgery (control group) were included in the study. After propensity score-matched analysis, patients were divided into two groups with 80 matched pairs each. The clinical, pathological, epidemiological, and radiological characteristics (evaluated through HRCT) of both groups were compared.Results: It was observed that Covid-19 patients presented more definite symptoms, were mostly younger men, and had higher BMI (body-mass index). After the radiological analysis of the matched patients, it was revealed that single lesion patients constituted 17% of Covid-19 cases and 89% of lung cancer cases. Patients in both groups mostly presented peripheral lesions. Covid-19 lesions had more lobes, segments and had various types with patchy forms. On the other hand, lung cancer tended to have only one type and had an oval form.Conclusion: Both Covid-19 and lung cancer showed ground-glass opacities with similar but independent characteristics. These characteristics combined with pathogen detection, short-term CT examination, and laboratory tests will aid in improved diagnosis.